Efeito do tempo de exposição nas temperaturas de 645°C e 820°C na corrosão localizada do aço inoxidável duplex UNS S31803 avaliado por espectroscopia de impedância eletroquímica - Faria, Eduardo Sarcinelli (2015)
In the present work were evaluated theelectrochemicalimpedance techniqueto detect the corrosion susceptibility of the UNS S31803 duplex stainless steel. This material was studied in the ‘as received’ condition (RC) and after heat treatment at temperatures of 645ºC and 820ºC, for times ranging from 4 hours, 8 hours and 12 hours. These treatments lead to precipitation, especially the sigma phase and also, chromium carbide and chromium nitrides. The study was performed using Double-loop Electrochemical Potenciokinect Reactivation (DL-EPR) method and Electrochemical Impedance Spectroscopy (EIS) in theOpen Circuit Potential (OCP) and just after film formation in a 2M H2SO4+ 0,5M NaCl + 0,01M KSCN solution. On the DL-EPR test it was found the presence of reactivation peaks in samples of 645ºC and 820ºC due to material sensitization. On the EIS test, were found inconsistent values for the charge transfer resistance (Rct) and a high value for Constant Phase Element (CPE) for the sample treated at 645ºC which indicates that there is more ion transport in these samples thanin the material treated at 820ºC. Values of inductance (L) and intermediate adsorption strength (Rads) were higher for the treated samples than for the ‘as received’ condition, leading to a misleadingthat the sample treated at 820ºC has a better corrosion resistance than the RC specimen. Due to this behavior, a correction was proposed in the area subject to corrosion so that the values are more plausible with the actual context